2019
DOI: 10.1080/23802359.2019.1693301
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome sequence of Pueraria thomsonii, an important traditional Chinese medicine plant

Abstract: Pueraria thomsonii is a leguminous plant with high root yield and starch content. It is also a medicinal material in the Chinese pharmacopeia. However, the raw materials of P. thomsonii are often confused with some non-medicinal Pueraria plants. To enrich the genetic resources of P. thomsonii and guide its molecular identification, the complete chloroplast genome was sequenced and reported. The total genome of P. thomsonii is 153,434 bp in length. consisting of two inverted repeat regions (IR S , 25,640 bp eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…However, the CP genomes of P. lobata and P. thomsonii have not been thoroughly studied. The complete CP genome of P. thomsonii has been reported [19], and we can use these data for subsequent experimental comparison and verification, and to conduct further analysis for the identification of the two species. Therefore, the comparative analysis and marker development of CP genome of Pueraria DC.…”
mentioning
confidence: 99%
“…However, the CP genomes of P. lobata and P. thomsonii have not been thoroughly studied. The complete CP genome of P. thomsonii has been reported [19], and we can use these data for subsequent experimental comparison and verification, and to conduct further analysis for the identification of the two species. Therefore, the comparative analysis and marker development of CP genome of Pueraria DC.…”
mentioning
confidence: 99%
“…lobata and P. montana var. thomsonii [ 18 20 ]. The GC content of these plastomes was 35.4%, except for P. mirifica A. Shaw and Suvat that was 35.5%.…”
Section: Resultsmentioning
confidence: 99%
“…To better determine the phylogenetic position of P. montana var. lobata and other varieties, we reconstructed a phylogeny using 47 chloroplast genomes, including the representatives of the major subclades of legume species referring to the previous studies [ 16 , 18 20 ]. Twenty-one previously published plastomes were downloaded from the NCBI GenBank database ( https://www.ncbi.nlm.nih.gov/ ) (Table S8).…”
Section: Methodsmentioning
confidence: 99%
“…Although Egan and Pan divided it into a new genus of Haymondia based on morphological characters and phylogenetic studies (Egan and Pan 2015;Egan et al 2016), it was still incomplete in molecular biology research. The accurate identification of H. wallichii can ensure the quality of H. wallichii (Miao et al 2019) and different molecular techniques may lead to different phylogenetic results (Zhang et al 2020). Therefore, the study reported the complete chloroplast genome of the H. wallichii, and revealed its phylogenetic relationship with other Fabaceae plants to lay the foundation for future research of Haymondia.…”
mentioning
confidence: 98%
“…The accurate identification of H. wallichii can ensure the quality of H. wallichii (Miao et al. 2019 ) and different molecular techniques may lead to different phylogenetic results (Zhang et al. 2020 ).…”
mentioning
confidence: 99%